2003
DOI: 10.1046/j.1532-5415.2003.51056.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival to Late Dementia in Dutch Nursing Home Patients

Abstract: One of seven nursing home patients with dementia survived to late dementia. Nursing home physicians can use these findings to inform relatives about the prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 15 publications
2
28
0
1
Order By: Relevance
“…This finding is in line with the study of Koopmans et al who found that these patient characteristics were predictors of survival to the final phase of dementia (Koopmans et al, 2003). Only 28% of the patients had a prescription of psychoactive medication.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with the study of Koopmans et al who found that these patient characteristics were predictors of survival to the final phase of dementia (Koopmans et al, 2003). Only 28% of the patients had a prescription of psychoactive medication.…”
Section: Discussionsupporting
confidence: 90%
“…Although not specifically studied, it is our experience that patients with other types of dementia also can survive to this final phase of dementia. We found in a large group of Dutch nursing home patients that 14% survived to the phase of late dementia (Koopmans et al, 2003). Furthermore, we found that the causes of death of these patients differed from those who died before reaching that phase .…”
Section: Introductionmentioning
confidence: 95%
“…Consequently, reporting of causes of death may vary not only by level of cognitive impairment, but may also be shaped by a medical environment-whether predominantly aimed at comfort or at cure. Therefore, with respect to the final phase of dementia (when patients have several total impairments; Koopmans et al, 2003), a debate on the question whether dementia is an immediate cause of death, or patients die of the consequences of dementia, is particularly relevant. Dementia as immediate cause of death is hardly reported on death certificates (Beard et al, 1996;Aevarsson et al, 1998;Ganguli and Rodrigues, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Survival of dementia patients is highly variable between individuals and also across studies with median survival from diagnosis or study entry of generally being between 5 and 9 years [16][17][18][19]. Variation across studies may be explained by different ways of defining onset of the dementia, and different age of the population under study, and by statistical adjustments.…”
Section: Death With Dementiamentioning
confidence: 99%